2022
DOI: 10.1186/s13046-022-02297-2
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic remodelling in human hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most frequent primary liver cancer, being the sixth most commonly diagnosed cancer and the fourth leading cause of cancer-related death. As other heterogeneous solid tumours, HCC results from a unique synergistic combination of genetic alterations mixed with epigenetic modifications.In HCC the patterns and frequencies of somatic variations change depending on the nearby chromatin. On the other hand, epigenetic alterations often induce genomic instability prone to mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 233 publications
1
45
1
1
Order By: Relevance
“…RNA modifications play a key role in regulating cell fate, an important regulator of HCC, in tumorigenesis and disease progression (Han et al, 2018;Pea et al, 2021;Braghini et al, 2022). The m6A, m7G, m5C, m1A, m3C, and ψ RNA modifications dynamically regulate the development of HCC, providing new strategies and possibilities for selecting possible therapeutic targets and investigating precisely directed intervention strategies for future HCC therapy (Tian et al, 2019;Bolatkan et al, 2022;Liu et al, 2022;Ren et al, 2022;Tong et al, 2022;Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA modifications play a key role in regulating cell fate, an important regulator of HCC, in tumorigenesis and disease progression (Han et al, 2018;Pea et al, 2021;Braghini et al, 2022). The m6A, m7G, m5C, m1A, m3C, and ψ RNA modifications dynamically regulate the development of HCC, providing new strategies and possibilities for selecting possible therapeutic targets and investigating precisely directed intervention strategies for future HCC therapy (Tian et al, 2019;Bolatkan et al, 2022;Liu et al, 2022;Ren et al, 2022;Tong et al, 2022;Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…HCC has a poor prognosis, making it crucial to investigate the molecular mechanisms and therapeutic strategies underlying hepatocellular carcinogenesis (Llovet et al, 2008;Chen et al, 2015). It has been shown that hepatocellular carcinogenesis is regulated by complex genetic and epigenetic mechanisms with pathophysiological processes involving viral and non-viral factors and influenced by fatty liver, immune cell infiltration, and the tumor microenvironment (Ozen et al, 2013;Han et al, 2018;Pea et al, 2021;Braghini et al, 2022). A study using whole-genome and -exome sequencing analysis has shown that epigenetic regulation is the most unusual differential modifier in HCC, with aberrant RNA modifications leading to differential gene expression, affecting the HCC formation and progression (Schulze et al, 2015;Klingenberg et al, 2017;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, histone modifications related to tumor formation and development have gradually attracted the attention of epigenetic researchers, and the increasing number of results indicate that tumors are often caused by histone modifications that affect their occurrence and prognosis ( 13 ). The epigenetic modifications offer ideal mechanisms for regulating gene expression and metabolic reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…Immortalized cells such as HeLa, HepG2, and Huh-7 cells have been widely used by researchers in the molecular biological sciences [1][2][3][4][5][6][7][8] because they are essentially identical cells that never change. The use of such cells has contributed to the study of tumor tissue formation at the molecular level.…”
Section: Introductionmentioning
confidence: 99%